The Position of the Departing Child Leaving His Parents in Inheritance According to Western Inheritance Law (Case Study of Surakarta District Court Decision Number 70/Pdt.G/2018/PN Skt) - Margareth; I Made Pria Dharsana (LEGAL BRIEF, 2022)
In Indonesia, there are no rules governing the termination of the relationship between parents and children, but the termination of the inheritance relationship between parents and children due to certain reasons is regulated in the Civil Code. In civil inheritance law, when a parent dies, the child is the heir of the parents, but if the child commits an inappropriate act as stipulated in Article 838 of the Civil Code, he is excluded from inheritance. In this study, to examine the position of children who leave their parents in inheritance according to western inheritance law based on the decision of the Surakarta District Court Number 70/Pdt.G/2018/PN Skt. The background of this research is that parents break the relationship and exclude their children from inheritance because they feel hurt and disappointed with children who leave their parents for 21 (twenty one) years. Based on the results of the research, it can be understood that in inheritance according to western inheritance law, it does not determine the legal consequences of the breakup of the parent-child relationship, the child will continue to inherit if he does not fulfill the reasons for inappropriate inheritance as regulated in Article 838 of the Civil Code.